2014
DOI: 10.1371/journal.pone.0116056
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analyses between a Spontaneous Late-Ripening Sweet Orange Mutant and Its Wild Type Suggest the Functions of ABA, Sucrose and JA during Citrus Fruit Ripening

Abstract: A spontaneous late-ripening mutant of ‘Jincheng’ (C. sinensis L. Osbeck) sweet orange exhibited a delay of fruit pigmentation and harvesting. In this work, we studied the processes of orange fruit ripening through the comparative analysis between the Jincheng mutant and its wild type. This study revealed that the fruit quality began to differ on 166th days after anthesis. At this stage, fruits were subjected to transcriptome analysis by RNA sequencing. 13,412 differentially expressed unigenes (DEGs) were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 52 publications
4
44
0
Order By: Relevance
“…Exogenous sucrose can accelerate the ripening of strawberry fruit [14]. In mutant sweet orange, which has a lower sucrose content, fruit ripening is delayed [40]. In the climacteric fruit tomato, exogenous sucrose treatment can promote postharvest fruit ripening by affecting its metabolism and enhancing ethylene synthesis and signal transduction [15].…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous sucrose can accelerate the ripening of strawberry fruit [14]. In mutant sweet orange, which has a lower sucrose content, fruit ripening is delayed [40]. In the climacteric fruit tomato, exogenous sucrose treatment can promote postharvest fruit ripening by affecting its metabolism and enhancing ethylene synthesis and signal transduction [15].…”
Section: Discussionmentioning
confidence: 99%
“…JAs have thus far been studied in the context of plant adaptive responses to various biotic and abiotic stresses (Zhang et al ., 2019). However, JA has also been shown to promote fruit ripening in citrus (Zhang et al ., 2014), strawberry (Concha et al ., 2013) and tomato (Liu et al ., 2012). This is consistent with the present findings as lemon fruit degreening was accompanied by an increase in the levels of JA-Ile (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The NCED1 were expressed only at the onset stage of ripening in peach and grape, when ABA content became high (Zhang et al, 2009a). Zhang et al (2014) studied the mechanism of a spontaneous late-maturing mutant of 'Jincheng' sweet orange and its wild type through the comparative analysis. The highest expression of CsNCED1 was at 215 DAA in WT.…”
Section: Discussionmentioning
confidence: 99%
“…ABA treatment can rapidly induced flavonol and anthocyanin accumulation in berry skins of the Cabernet Sauvignon grape suggesting that ABA could stimulate berry ripening and ripening-related gene expression (Koyama et al, 2010). ABA also participated in the regulation of fruit development and ripening of tomato (Zhang et al, 2009b;Sun et al, 2011), cucumber (Wang et al, 2013), strawberry (Jia et al, 2011), bilberry (Karppinen et al, 2013), citrus (Zhang et al, 2014) and grape (Nicolas et al, 2014). Recent studies showed that ABA is a positive regulator of ripening and exogenous ABA application could effectively regulate citrus fruit maturation (Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation